The Impact of Commitment to Applying International Standards for Internal Auditing in Improving the Level of Internal Audit : Performance in Economic Units in Erbil Governorate - Kurdistan Region of Iraq - Tavga Mahdi Azeez; Awat Jahfer AbdulMajeed; Hawar Ghafur Hamadamin (QALAAI ZANIST JOURNAL, 2021)
The study aimed to identify the concept, importance and objectives of internal auditing and international standards for internal auditing, in addition to showing the impact of adherence to international standards for internal auditing on improving the level of performance of internal auditing. The study problem was represented in (Is there a statistically significant relationship and effect between commitment to applying international standards for internal auditing and improving the level of internal auditing?) The study followed the descriptive and analytical method. Data were collected using a questionnaire form, and it was analyzed by statistical and mathematical methods. The study sample consisted of a group of employees of economic units in Erbil governorate represented by (internal and external auditors) and university teachers. The most prominent results of the study were that internal auditing was based on the need for it, and its development was in parallel with the economic development. The study also showed the existence of a statistically significant relationship and effect between commitment to applying international standards for internal auditing and improving the performance level of internal auditing.